On the Propagation of Generalized Thermoelastic Vibrations in Plates - Verma, K.L.; Hasebe, N. (Engineering Transactions, 1999)
The heat conduction equation in the context of generalized theories of thermoelasticity is used to study the propagation of plane harmonic waves in a thin, flat, infinite, homogeneous, thermoelastic isotropic plate of finite width. The frequency equations corresponding to the symmetric and antisymmetric modes of vibration of the plate are obtained, and some limiting cases of the frequency equations are then discussed. The comparison of the results for the theories of generalized thermoelasicity have also been made. The results obtained have been verified numerically and are represented graphically for aluminum epoxy composite plate.